A photosynthetic-mineralizing bio-composite material, and a method of making and using the same
Patent Information
- Application Number
- CN202611345599.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]为解决现有技术中现有的产氧系统依赖材料自身的化学分解或物理溶解释放氧气,释氧速率和持续时间由材料固有属性决定,无法响应外部信号进行动态调控,导致氧释放行为与组织修复进程相互独立且无法协同的问题,本发明提供了一种光合-矿化生物复合材料及其制备方法和应用
1、本发明提供了一种光合-矿化生物复合材料。本发明提供的该光合-矿化生物复合材料是将上转换发光纳米颗粒与经仿生锌矿化修饰的藻细胞封装于由经光交联固化形成甲基丙烯酰化海藻酸钠水凝胶微球中。本发明提供的该光合-矿化生物复合材料具有光控氧锌时序释放的效果,该效果源于材料内在的“光控开关”机制:上转换发光纳米颗粒作为光能转换器,将近红外光转换为聚球藻光合作用可利用的红光,实现外部光控下的深层组织生物产氧;聚球藻细胞表面仿生矿化形成的锌外壳则作为储锌库,其稳定性直接受聚球藻活性的调控——光照时聚球藻存活,锌外壳维持稳定,Zn2+释放维持较低水平;撤光后聚球藻逐渐失活裂解,锌外壳随之降解,Zn2+释放速率提高。由此,供氧与释锌在同一体系中通过光照“开/关”实现时序性主动切换,而非简单的功能叠加,从而可以解决现有技术中无法协同放射性颌骨坏死缺氧微环境改善与组织修复的问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical composite materials technology, specifically relating to a photosynthetic-mineralized biocomposite material, its preparation method, and its application. Background Technology
[0002] Osteonecrosis of the jaw (ORNJ) is a major clinical challenge faced by head and neck cancer patients undergoing radiotherapy, characterized by persistent bone necrosis and impaired healing in previously irradiated tissues. Current understanding of ORNJ is primarily based on the classic hypoxia, hypovascularization, and hypocellularity (the "three lows") theory: high-dose radiation severely damages the local microvascular system, reducing tissue perfusion and creating a hypoxic microenvironment; due to the relatively limited blood supply to the jawbone itself, radiation-induced vascular damage further exacerbates local hypoxia; this adverse microenvironment accelerates cell loss and aging, impairs regenerative capacity, and hinders effective bone repair. These interconnected pathological changes collectively form a self-perpetuating microenvironment, hindering sustained tissue recovery. Therefore, reshaping the "three lows" microenvironment is a core requirement for achieving effective ORNJ treatment.
[0003] Current clinical treatment options, including hyperbaric oxygen therapy (HBO) and traditional bone grafting, can temporarily increase local oxygen partial pressure, promote wound healing, or provide structural support, but they cannot systematically improve the hypoxic, hypo-, and hypo-hypoxic microenvironment in a spatially and temporally coordinated manner. This limitation has prompted increasing attention from the academic community to biomaterials capable of sustained oxygen production. Existing oxygen production systems, such as those based on metal peroxides or perfluorocarbons, have been used to improve local oxygen supply levels in ischemic or bone defect tissues. These systems rely on the chemical decomposition or physical dissolution of the material itself to release oxygen; the oxygen release rate and duration are determined by the inherent properties of the material and cannot be dynamically regulated in response to external signals. This results in oxygen release behavior being independent of and unable to coordinate with the tissue repair process. Summary of the Invention
[0004] To address the problem that existing oxygen-generating systems rely on the chemical decomposition or physical dissolution of materials to release oxygen, with the release rate and duration determined by the inherent properties of the material, and cannot be dynamically regulated in response to external signals, resulting in oxygen release behavior being independent of and unable to coordinate with tissue repair processes, this invention provides a photosynthetic-mineralization biocomposite material, its preparation method, and its applications. To achieve the above objectives, this invention adopts the following technical solution:
[0005] The first objective of this invention is to provide a photosynthetic-mineralized biocomposite material (UBMR@Zn composite material), which is prepared by encapsulating upconversion luminescent nanoparticles and biomimetic zinc mineralization-modified algal cells in a carrier matrix using microfluidic technology; the mass ratio of the upconversion luminescent nanoparticles, biomimetic zinc mineralization-modified algal cells, and carrier matrix is 1:0.1~1.5:15~22.
[0006] The upconversion luminescent nanoparticles (infrared-responsive UCNPs) are prepared by a hydrothermal method using rare earth nitrates (Y(NO3)3, Yb(NO3)3, Er(NO3)3), sodium citrate solution, and sodium fluoride solution as raw materials. These upconversion luminescent nanoparticles can convert 980nm near-infrared light into approximately 680nm localized red light. The mass ratio of the rare earth nitrates, sodium citrate, and sodium fluoride is 1:3~7:1~2.
[0007] The biomimetic zinc mineralization modified algal cells (biomimetic zinc mineralized PCC 7942 cells, Synechococcus PCC 7942) were obtained by depositing a zinc-containing mineral shell on the surface of Synechococcus cells. The biomimetic zinc mineralization modification was achieved by forming a zinc-containing mineral shell on the surface of Synechococcus cells.
[0008] The carrier matrix is a sodium alginate hydrogel microsphere formed by photocrosslinking and curing of a sodium alginate prepolymer, which is used to encapsulate the upconversion luminescent nanoparticles and the algal cells modified with biomimetic zinc mineralization.
[0009] The upconversion luminescent nanoparticles and the biomimetic zinc-mineralized algal cells are loaded onto methacryloylated sodium alginate hydrogel microspheres. Under 980nm near-infrared light irradiation, the localized red light emitted by the upconversion luminescent nanoparticles can activate the photosynthesis of *Symplocos lumbricoides* to produce oxygen on demand. After the light irradiation is removed, the activity of *Symplocos lumbricoides* decreases, causing the zinc-mineralized shell to degrade and release Zn. 2+ .
[0010] This invention utilizes highly penetrating near-infrared light to activate upconversion luminescent nanoparticles within deep tissues. After absorbing near-infrared light, these nanoparticles release red light that can be utilized by Synechococcus cells for photosynthesis, driving oxygen production through photosynthesis. This achieves localized oxygen release from deep tissues under external light control, improving the hypoxic microenvironment. Upon removal of light, the Synechococcus cells experience reduced activity due to the lack of light energy, and their altered metabolic state promotes the degradation of their surface zinc mineralization shell, resulting in delayed release of zinc ions. This zinc ion exerts a positive angiogenic and osteogenic effect, promoting tissue repair. Therefore, this invention achieves temporal active regulation of the oxygen supply and repair phases within the same material system through the "on / off" switching of an external light-controlled signal, solving the technical problem in existing oxygen production systems where oxygen release behavior and tissue repair processes are independent and cannot be coordinated.
[0011] Furthermore, the particle size of the methacryloylated sodium alginate hydrogel microspheres is 200 μm to 250 μm.
[0012] Furthermore, the density of the *Polychocinoma* cells in the sodium methacrylamide hydrogel microspheres is 10. 8 cells / mL ~10 11 The concentration of the upconversion luminescent nanoparticles in the sodium methacryloyl alginate hydrogel microspheres is 0.1 mg / mL to 100 mg / mL.
[0013] Furthermore, the Synechococcus cells are slender Synechococcus ( Synechococcus elongatus PCC 7942 strain. The slender Synechococcus strain PCC 7942 is simply referred to as PCC 7942 strain or PCC 7942.
[0014] A second object of the present invention is to provide a pharmaceutical composition comprising the photosynthetic-mineralized biocomposite material and a pharmaceutically acceptable carrier.
[0015] Furthermore, the dosage form of the pharmaceutical composition is selected from injectable microsphere suspensions, pre-formed three-dimensional scaffolds, or malleable bone filler pastes.
[0016] A third objective of this invention is to provide a method for preparing the aforementioned photosynthetic-mineralized biocomposite material, comprising the following steps: Synechococcus cells were cultured to the logarithmic growth phase, and the culture was collected by centrifugation. The lower cell pellet was collected and resuspended in a Zn-containing solution. 2+ The algal cells were stirred in a buffer solution for 12-48 hours. Then, sodium hydroxide solution was added to adjust the pH to approximately 8.4-8.6. The reaction was continued for 0.5-1.5 hours, and the algal cells modified by biomimetic zinc mineralization were collected by centrifugation.
[0017] Rare earth nitrates were added to sodium citrate solution and stirred to dissolve. Then, sodium fluoride solution was added to fluorinate the precipitate. After high-temperature reaction and washing of the precipitate, the upconversion luminescent nanoparticles were obtained.
[0018] Algal cells modified with biomimetic zinc mineralization, upconversion luminescent nanoparticles, and sodium methacrylamide prepolymer were mixed and microdroplets were generated through a microfluidic device. After photocrosslinking and curing, sodium methacrylamide hydrogel microspheres encapsulating algal cells modified with biomimetic zinc mineralization and upconversion luminescent nanoparticles were formed.
[0019] The methacrylated sodium alginate hydrogel microspheres were collected, and the unencapsulated material was washed away to obtain the photosynthetic-mineralized biocomposite material, namely UBMR@Zn composite material, or simply UBMR@Zn.
[0020] Among them, the photosynthetic-mineralized biocomposite material is also known as the upconversion-assisted biomixed microreactor.
[0021] Furthermore, the microfluidic device employs a coaxial flow or T-channel design, with a dispersed phase flow rate of 10 μL / min to 50 μL / min and a continuous phase flow rate of 100 μL / min to 400 μL / min. The generated microdroplets are exposed to light at a wavelength of 405 nm (power 10 mW / cm²). 2 ~50mW / cm 2 Crosslinking for 30 to 120 seconds under the specified conditions.
[0022] Furthermore, the Zn-containing 2+ Zn in the buffer solution 2+ The concentration ranges from 0.1 μmol / L to 40 μmol / L.
[0023] A fourth object of the present invention is to provide the use of the photosynthetic-mineralized biocomposite material or the pharmaceutical composition in the preparation of implant materials for treating radiation-induced bone defects, radiation-induced osteonecrosis, osteoporotic fractures or ischemic osteonecrosis.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention provides a photosynthetic-mineralization biocomposite material. The photosynthetic-mineralization biocomposite material provided by this invention encapsulates upconversion luminescent nanoparticles and algal cells modified with biomimetic zinc mineralization within methacrylamide sodium alginate hydrogel microspheres formed by photocrosslinking and curing. This photosynthetic-mineralization biocomposite material provides the effect of photocontrolled sequential release of oxygen and zinc. This effect originates from the material's inherent "photocontrolled switch" mechanism: the upconversion luminescent nanoparticles act as a light energy converter, converting near-infrared light into red light usable by Synechococcus photosynthesis, achieving deep tissue bio-oxygenation under external light control; the zinc shell formed by biomimetic mineralization on the surface of Synechococcus cells acts as a zinc reservoir, its stability directly regulated by the activity of Synechococcus—Synechococcus survives under light, the zinc shell remains stable, and Zn... 2+ Release remained at a low level; after light removal, Synechococcus gradually became inactive and lysed, and the zinc shell degraded accordingly, releasing Zn. 2+ The release rate is increased. Thus, oxygen supply and zinc release are actively switched sequentially within the same system through the "on / off" of light, rather than simply superimposed functions. This solves the problem in existing technologies that cannot synergistically improve the hypoxic microenvironment and tissue repair in radiation-induced osteonecrosis of the jaw.
[0025] 2. Osteonecrosis of the jaw (ORNJ) is a serious complication following radiotherapy for head and neck cancers. Its progression is characterized by a persistent hypoxic, hypovascularized, and sparsely cellular microenvironment, which not only limits the tissue's endogenous repair capacity but also reduces the efficacy of traditional regenerative therapies. To address this challenge, this invention proposes a phased oxygenation-angiogenesis-osteoogenesis (OAO) strategy aimed at restoring the microenvironment of irradiated bone in a time-controlled manner. This study utilizes biomimetic zinc-mineralized algal cells (biomimetic zinc-mineralized Synechococcus cells / biomimetic zinc-mineralized PCC 7942) to develop an upconversion-assisted biohybrid microreactor (UBMR@Zn), which integrates upconversion luminescent nanoparticles for photoactivation. This biohybrid system is encapsulated in microfluidically generated sodium alginate hydrogel microspheres. The mineralized PCC 7942 serves as the core bioactive unit, responding to light to generate oxygen and delaying zinc ion release. Under 980nm near-infrared (NIR) irradiation, PCC 7942 can produce oxygen on demand under localized red light stimulation; after the light is removed, the reduced activity of PCC 7942 promotes the degradation of the mineralized zinc shell and releases Zn. 2+ This design achieves programmable, sequential oxygen and zinc transport through NIR regulation: in the early stages of photoactivation, NIR-triggered oxygen production alleviates hypoxia and improves cell viability. In the later stages of the dark period, Zn is continuously released. 2+It can promote angiogenesis and osteogenic differentiation of endothelial cells. In the rat ORNJ model, UBMR@Zn improved local perfusion, enhanced vascular remodeling, and promoted vascularized bone regeneration. Overall, UBMR@Zn provides a microenvironment-centric therapeutic strategy for treating radiation-induced bone defects. Attached Figure Description
[0026] Figure 1 This invention relates to the design, preparation, and characterization of UBMR@Zn microspheres (UBMR@Zn); wherein: a is a schematic diagram of the preparation of UBMR@Zn: First, PCC 7942 was zinc mineralized using a biomimetic mineralization method to obtain PCC@Zn; then, PCC@Zn and UCNPs were co-encapsulated in AlgMA hydrogel microspheres using microfluidic droplet generation and photocrosslinking technology. b represents PCC 7942 cells treated with different Zn²⁺ concentrations and then cultured for 7 days (n=3), based on OD... 680 The value of the assessed concentration is 1×10 9 Growth and photosynthetic activity of PCC 7942 cells / mL; c represents the determination of different Zn values by ICP-MS. 2+ PCC@Zn prepared at a certain concentration of Zn 2+ Load (n=3); d represents the Zeta potential curves of the original PCC 7942 and PCC@Zn, showing the change in surface charge after zinc mineralization; e shows the TEM image and corresponding EDS elemental distribution map of PCC@Zn, indicating the formation of a zinc-bearing mineral layer on the surface of PCC 7942; scale bar = 1 μm. f represents the XRD patterns of PCC 7942 and PCC@Zn; g represents 1×10 under illumination conditions. 9 Oxygen production activity of natural PCC 7942 and PCC@Zn per cell / mL (n=3); h represents the photoluminescence emission spectrum of UCNPs under 980 nm NIR excitation and the absorption spectrum of PCC 7942, showing that there is an overlap between the emission spectrum of UCNPs and the chlorophyll absorption spectrum of PCC 7942; i is a schematic diagram of UBMR@Zn microfluidic control equipment; j represents the optimization study of oxygen production efficiency of microspheres prepared with different concentrations of PCC@Zn and UCNPs; k is a bright-field and fluorescence image of UBMR@Zn, showing its spherical morphology and the uniform distribution of PCC 7942 in the hydrogel matrix; scale bar = 100 μm; l represents the diameter distribution of UBMR@Zn microspheres; m is a scanning electron microscope image of UBMR@Zn microspheres (left: scale bar = 50µm; right: scale bar = 1µm), showing the morphology of the microspheres and the PCC 7942 structure embedded in the hydrogel network; Data are expressed as mean ± standard deviation; statistical significance was determined using one-way ANOVA;* p <0.05,** p <0.01, **** p <0.0001; Abbreviations: AlgMA—Sodium methacrylamide; EDS—Energy Dispersive X-ray Spectroscopy; ICP-MS—Inductively Coupled Plasma Mass Spectrometry; SEM—Scanning Electron Microscopy; TEM—Transmission Electron Microscopy; UCNPs—Upconversion Luminescent Nanoparticles; XRD—X-ray Diffraction.
[0027] Figure 2 This invention relates to UBMR@Zn in staged oxygen production and delayed Zn production. 2+ Analysis of the functional characteristics of release; including: Image a shows a representative fluorescence image during the incubation of UBMR@Zn microspheres, demonstrating the maintenance of PCC 7942 activity within the microspheres over time. Scale bar = 200 μm;
[0028] b represents the quantitative analysis of the autofluorescence intensity of PCC 7942 in UBMR@Zn microspheres during incubation (n=3); c represents the DCFH fluorescence imaging results of BMR@Zn and UBMR@Zn microspheres under 980nm NIR irradiation; scale bar = 200μm. d is a schematic diagram of the phased treatment scheme: In the early stage, NIR irradiation is applied to activate photosynthetic oxygen production; subsequently, Zn... 2+ The release phase is dominant and NIR irradiation is not performed; e represents the sequential oxygen production of UBMR@Zn microspheres and Zn 2+ The release curves show early NIR-triggered oxygen production and delayed Zn release. 2+ Release (n=3); f is a schematic diagram of the in vitro microenvironment model of ORNJ sample cultured under hypoxic conditions with UBMR@Zn microspheres and irradiated cells in the Transwell co-culture system. g shows representative fluorescence images of hypoxia staining in irradiated MC3T3-E1 cells cultured under hypoxic conditions after different treatments. Scale bar = 100 μm;
[0029] h represents the quantitative analysis of the fluorescence intensity of the hypoxia probe (n=3). i represents representative fluorescence images of intracellular zinc content detected using a zinc-sensitive probe in irradiated MC3T3-E1 cells after different treatments; scale bar = 20 μm; j represents the quantitative analysis of intracellular zinc fluorescence intensity (n=3); Data are expressed as mean ± standard deviation. Statistical significance was determined using a Student's t-test or one-way ANOVA, depending on the circumstances. p <0.05,** p <0.01, **** p <0.0001. Abbreviations: DCFH, 2′,7′-dichlorodihydrofluorescein; NIR, near-infrared; ORNJ, radioactive osteonecrosis of the jaw; PCC@Zn, PCC 7942, zinc mineralization.
[0030] Figure 3 For the sequential delivery of oxygen and Zn by UBMR@Zn in this invention 2+ Effects on in vitro cell survival, angiogenesis activity, and osteogenic activity; among which: a shows representative images of live / dead staining of MC3T3-E1 cells after different treatments: live cells are green and dead cells are red; scale bar = 200 μm. b represents the results of quantitative analysis of live / dead staining (n=3); c shows representative fluorescence images of mitochondrial membrane potential in MC3T3-E1 cells after different treatments: green represents JC-1 monomers (low ΔΨm value); red represents JC-1 aggregates (high ΔΨm value); scale bar = 20 μm; d represents the quantitative results of mitochondrial membrane potential (expressed as the ratio of JC-1 red / green fluorescence intensity, n=3); e represents a representative image of tubular structures formed by EPC on the matrix gel under different treatment conditions; scale bar = 200 μm; f represents a quantitative analysis of the number of connection points in the tubular structure formation experiment (n=3). g represents representative images of EPC scratch healing experiments at 0h and 12h under different treatment conditions; scale bar = 200μm. Quantitative analysis of EPC cell wound closure rate when h is 12h (n=3). i represents ALP staining images of MC3T3-E1 cells after 7 days of osteogenic induction under different treatment conditions; j represents the quantitative analysis of ALP staining intensity (n=3); k represents ARS staining images of MC3T3-E1 cells after 21 days of osteogenic induction under different treatment conditions; l represents the quantitative analysis of mineralized nodule formation based on ARS staining results (n=3). m represents the relative mRNA expression level of HIF-1α in MC3T3-E1 cells (n=3). n represents the relative OSX mRNA expression level in MC3T3-E1 cells (n=3). o represents the relative mRNA expression level of RUNX2 in MC3T3-E1 cells (n=3). p represents the relative mRNA expression level of BMP2 in MC3T3-E1 cells (n=3). q represents the relative mRNA expression level of OPN in MC3T3-E1 cells (n=3); Data are expressed as mean ± standard deviation. Statistical significance was determined using one-way ANOVA. p <0.05,** p <0.01, *** p <0.001, **** p <0.0001; Abbreviations: ALP, alkaline phosphatase; ARS, alizarin red S; BMP2: bone morphogenetic protein 2; EPCs: endothelial progenitor cells; HIF-1α: hypoxia-inducible factor 1α; OPN: osteopontin; OSX: osteoblast-specific transcription factor; RUNX2: Runt-related transcription factor 2.
[0031] Figure 4 This invention relates to the effects of UBMR@Zn on hypoxia and vascular remodeling in a rat ORNJ model; wherein: Figure a shows a schematic diagram of the rat ORNJ model and the phased in vivo treatment regimen, including fractionated mandibular irradiation, molar extraction, microsphere implantation, early NIR activation for oxygen production, and subsequent Zn treatment. 2+ The main focus was on the repair process and sample collection in week 6; b shows representative images of mandibular bone defect tissue from different groups, stained with pipemnidazole immunohistochemically, indicating tissue hypoxia; scale bar = 100 μm. c represents the quantitative analysis of the positive areas for pipemnidazole (n=3). d shows representative immunofluorescence staining images of HIF-1α in mandibular bone defect tissue from different groups; scale bar = 50 μm; e represents the quantitative analysis of HIF-1α fluorescence intensity (n=3); f shows representative immunofluorescence staining images of CD31-positive vascular structures in mandibular bone defect tissues from different groups; scale bar = 50 μm. g represents the quantitative analysis of CD31 fluorescence intensity (n=3); h represents the laser speckle contrast imaging results of local mandibular blood flow perfusion in different groups; scale bar = 2cm; i represents quantitative analysis of relative blood flow in the mandibular region (n=3). Data are expressed as mean ± standard deviation. Statistical significance was determined using one-way ANOVA. p <0.05,** p <0.01, *** p <0.001, **** p <0.0001; Abbreviations: CD31—differentiation cluster 31; HIF-1α—hypoxia-inducible factor 1α; NIR—near-infrared; ORNJ—radiation-induced osteonecrosis of the jaw.
[0032] Figure 5 This invention relates to the effect of UBMR@Zn on alveolar socket healing and bone regeneration at irradiated mandibular bone defects; wherein: a shows a representative gross image of the extraction socket area at week 6 after implantation of different materials, showing the mucosal healing and exposed bone condition; scale bar = 1 mm; b shows representative 3D CT reconstructed images of the mandibular extraction socket region in different groups; scale bar = 1 mm. c represents the quantitative CT analysis results of BV / TV (n=3); d represents the quantitative CT analysis results of BMD (n=3); e represents the quantitative CT analysis result of Tb.N (n=3); f represents the quantitative CT analysis results of Tb.Th (n=3); g shows representative H&E stained images of mandibular bone defect tissue from different groups, showing alveolar socket healing and new bone formation; scale bar = 200 μm or 50 μm. h represents representative Masson trichrome stained images of mandibular bone defect tissue from different groups, showing the distribution of collagen deposition and matrix structure; scale bar = 200 μm or 50 μm; i represents representative immunofluorescence staining images of RUNX2 protein in mandibular bone defect tissues from different groups, with arrows indicating areas of strong fluorescence signal; scale bar = 50 μm; j represents the quantitative analysis result of RUNX2 fluorescence intensity (n=3); Data are expressed as mean ± standard deviation. Statistical significance was determined using one-way ANOVA. p <0.05,** p <0.01, *** p <0.001, **** p <0.0001; Abbreviations: BMD, bone mineral density; BV / TV, bone volume fraction; H&E, hematoxylin-eosin staining; micro-CT, micro-computed tomography; RUNX2, Runt-related transcription factor 2; Tb.N, number of trabeculae; Tb.Th, trabecular thickness.
[0033] Figure 6 Representative H&E staining images of the lungs, liver, spleen, kidneys, and heart from the control group, UBMR group, BMR@Zn group, and UBMR@Zn group were used to assess the biocompatibility of UBMR@Zn in this invention. No obvious histopathological abnormalities, including inflammatory infiltration, tissue necrosis, hemorrhage, or structural destruction, were observed in the major organs, supporting the preliminary safety of UBMR@Zn in vivo. Scale bar = 100 μm (n = 3).
[0034] Figure 7 This is a schematic diagram illustrating the formation of UBMR@Zn in this invention. Detailed Implementation
[0035] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments, but this should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following embodiments are commercially available unless otherwise specified.
[0036] Example 1 I. Methods 1. Preparation of UBMR@Zn composite materials (1) Slender Synechococcus ( Synechococcus elongatus PCC 7942 strain (abbreviated as PCC 7942 strain or PCC 7942) was cultured in BG11 medium (Qingdao Haibo Biotechnology) under a 12h light / 12h dark cycle until it reached a growth rate of 1×10⁻⁶. 9 Cells / mL, take 25 mL of bacterial suspension and centrifuge at 3000 rpm for 5 min to collect cell pellet, then wash three times with phosphate-buffered saline (PBS) (0.1 M, pH 7.3 ± 0.1, Propofol) to obtain PCC 7942 pellet.
[0037] Among them, strain PCC 7942 was purchased from the Institute of Hydrobiology, Chinese Academy of Sciences (Wuhan, Hubei Province, China).
[0038] (2) The preparation method of zinc mineralized PCC 7942 (synechococcus cells modified with biomimetic zinc mineralization / algal cells modified with biomimetic zinc mineralization / PCC 7942 cells modified with biomimetic zinc mineralization / zinc mineralized PCC 7942, PCC@Zn) is as follows: The obtained PCC7942 precipitate was resuspended in PBS containing 20 μmol / L ZnCl2 (Z112534, Shanghai Aladdin Company) and stirred overnight; then 1 mM sodium hydroxide solution (S774711, Aladdin Company) was added dropwise to adjust the pH to 8.5 and stirred for 1 h; finally, the obtained zinc mineralized PCC 7942 (PCC@Zn) was collected by centrifugation and washed three times with PBS.
[0039] Overnight stays refer to stays of 12 hours or more.
[0040] (3) The preparation method of sodium alginate (AlgMA) with methacrylamide is as follows: 5g of sodium alginate (A434498, Aladdin) was dissolved in 50mL of PBS and stirred at 60°C. Then, 8mL of methacrylic anhydride (M102519, Aladdin) was slowly added, and the reaction was carried out at 50°C for 4h. During the reaction, sodium hydroxide solution was used to maintain the pH between 8 and 9. After the reaction was completed, 200mL of PBS was added to terminate the reaction. The resulting solution was dialyzed for 7 days using a dialysis membrane with a molecular weight cutoff of 8000Da~14000Da, and then freeze-dried to obtain AlgMA.
[0041] (4) UCNPs (upconversion luminescent nanoparticles / NaYF4:Yb 3+ Er 3+ The preparation method is as follows: Weigh 5.8g of sodium citrate (S189183, Aladdin) into a clean beaker, then add 25mL of ultrapure water and dissolve by sonication. Then weigh 0.7445g of Y(NO3)3 (Y118878, Aladdin), 0.3054g of Yb(NO3)3 (Y118479, Aladdin), and 0.0128g of Er(NO3)3 (E106128, Aladdin) and add them to the above solution, dissolve by sonication, and stir magnetically for 30min. Then weigh 1.26g of sodium fluoride and dissolve it in 25mL of ultrapure water, then add the sodium fluoride aqueous solution dropwise to the above mixed solution, continue to stir magnetically for 10min, then transfer the mixed solution to a 60mL reaction vessel, and then place the reaction vessel in an oven at 180°C and heat for 12h. The product was then centrifuged, washed three times with deionized water, and then dried in a 60°C vacuum drying oven.
[0042] (5) To prepare the UBMR@Zn composite material (photosynthetic-mineralized biocomposite material), the previously prepared PCC@Zn and UCNPs were dispersed in a 2wt% sodium methacrylamide solution as the aqueous phase. Monodisperse microspheres were prepared using a microfluidic droplet generation system with volatile droplet generating oil (YX-HFY-231215050, Yixin Life Science Co., Ltd., Shenzhen, Guangdong, China) as the oil phase. The flow rates of the aqueous phase and the oil phase were set to 30 μL / min and 250 μL / min, respectively. The obtained microspheres were photocrosslinked for 90 seconds at 20 mW power using a multifunctional curing device (YXMC-01, Yixin Life Science Co., Ltd.), washed with PBS, and collected to obtain the UBMR@Zn composite material.
[0043] A schematic diagram of the formation of UBMR@Zn is shown below. Figure 7 As shown.
[0044] 2. Characterization of UBMR@Zn composite materials (1) Optimization of zinc loading PCC@Zn prepared with ZnCl2 at concentrations ranging from 0.1 μmol / L to 40 μmol / L was redissolved in 25 mL of BG11 medium and cultured for 7 days. OD values were measured using a microplate reader. 680 To assess the impact of zinc mineralization on the growth of PCC 7942, 20 mL of PCC@Zn solution was centrifuged and lyophilized. The zinc content in each sample was quantified by inductively coupled plasma mass spectrometry (ICP-MS), and the zinc loading was calculated and optimized based on the zinc concentration per mL of dissolved PCC@Zn suspension to obtain PCC@Zn that retains normal photosynthetic activity while achieving the highest zinc loading.
[0045] (2) Characterization of PCC@Zn The morphology of PCC 7942 and PCC@Zn was examined using transmission electron microscopy (JEM-F200, JEOL, Tokyo, Japan). Elemental composition and spatial distribution were analyzed using energy-dispersive X-ray spectroscopy. The crystal composition of zinc mineral deposits on the PCC 7942 surface was characterized by X-ray diffraction (SmartLab SE, Rigaku, Tokyo, Japan). To examine whether zinc mineralization affects oxygen production in PCC 7942, the cells were cultured to 1×10⁻⁶. 9 PCC 7942 suspensions at cell / mL and the optimal PCC@Zn suspension obtained above (1) were exposed to light. Dissolved oxygen levels were measured using a portable dissolved oxygen meter (JPB-70A, Qiwei Instruments, Hangzhou, China).
[0046] (3) Characterization, oxygen production and Zn of UBMR@Zn 2+ Release assessment The morphology and size of UBMR@Zn were observed using a fluorescence stereomicroscope (M205FA, Leica, Wetzlar, Germany). The distribution of PCC@Zn within UBMR@Zn was examined using a scanning electron microscope (S-4800, Hitachi, Tokyo, Japan).
[0047] For oxygen production assessment, 1 g of freshly prepared UBMR@Zn was resuspended in 10 mL of deoxygenated water. The deoxygenated water was prepared by vacuum treatment and nitrogen purging for 1 h before use to obtain the UBMR@Zn suspension. The UBMR@Zn suspension was immediately transferred to a sealed container to maintain an anaerobic environment and irradiated with 300 mW / cm² at 980 nm near-infrared irradiation for 60 min daily. Dissolved oxygen levels were monitored every 2 days using a portable dissolved oxygen meter for 28 days. The container was resealed immediately after each measurement.
[0048] For Zn 2+Release assessment was performed by preparing another UBMR@Zn suspension under the same conditions. At each time point, 1 mL of the supernatant was collected, and the released zinc was quantified by inductively coupled plasma mass spectrometry (ICP-MS; 7850, Agilent, Santa Clara, USA). After each sampling, 1 mL of fresh deoxygenated water was added to maintain a total volume of 10 mL. Zn²⁺ release was monitored every 2 days for 28 days.
[0049] (4) Imaging of photoactivated oxygen-related activities by DCFH-DA DCFH-DA (HY-D0940, MedChemExpress, Monmouth, USA) was used as an indirect fluorescent indicator of photoactivated oxygen-related activity in UBMR@Zn. UBMR@Zn was placed in a confocal culture dish and incubated in the dark for 24 h. The sample was then incubated with 10 μg / mL DCFH-DA for 5 min and irradiated with 300 mW / cm² at 980 nm near-infrared for 10 min. Fluorescence images were acquired using a confocal laser scanning microscope (A1R Plus, Nikon, Tokyo, Japan), followed by three-dimensional reconstruction analysis.
[0050] 3. In vitro assessment (1) Establishment of an in vitro ORNJ-like cell model MC3T3-E1 cells and endothelial progenitor cells were cultured at 37°C in a humidified incubator containing 5% (v / v) CO2 and in α-minimum essential medium (α-MEM) supplemented with 10% (v / v) fetal bovine serum and 1% (v / v) penicillin-streptomycin. ORNJ-like cell models were constructed by irradiating MC3T3-E1 cells and mouse bone marrow-derived endothelial progenitor cells with X-rays at a dose rate of 2 Gy / min using a biological X-ray irradiator (Sharp 100, Ruishi, Hefei, Anhui, China) with 8 Gy. The cells were then further cultured under hypoxic conditions containing 1% (v / v) O2.
[0051] MC3T3-E1 cells were purchased from Procell Life Sciences Co., Ltd. (Wuhan, Hubei, China). Mouse bone marrow-derived endothelial progenitor cells (EPCs) were purchased from Jennio Biotech (Catalog No. JNO-M0242, Guangzhou, Guangdong, China).
[0052] (2) Assessment of cellular hypoxia Image-iT Green hypoxia reagent (I14834, Thermo Fisher Scientific, Waltham, USA) was used to evaluate the ability of UBMR@Zn to alleviate cellular hypoxia. MC3T3-E1 cells treated in step (1) above were incubated with 5 μM Image-iT Green hypoxia reagent for 3 h. During incubation, the cells were irradiated with 980 nm near-infrared light at 300 mW / cm². 2 Irradiate for 20 minutes. After incubation, wash the cells three times with PBS and observe them using a confocal laser scanning microscope.
[0053] (3) Detection of intracellular zinc ions Intracellular zinc levels were assessed using the cell membrane-permeable zinc fluorescent probe Zinpyr-1 (MX4550-1MG, Maokang Biotechnology, Shanghai, China). UBMR@Zn synthesized according to the method described in Example 1 was pre-incubated in the dark for 14 days and co-cultured with MC3T3-E1 cells for 6 h. Cells were then washed three times with PBS and incubated with medium containing 10 μM Zinpyr-1 at 37°C for 30 min. Fluorescence images were acquired using a confocal laser scanning microscope.
[0054] (4) Calcein-AM / PI live / dead cell staining Cell viability was visualized using the Calcein-AM / PI live / dead cell staining kit (C2015S, Beyotime). Calcein-AM fluoresced live cells in green, while propidium iodide fluoresced dead cells in red. MC3T3-E1 cells were seeded in 24-well plates and treated as specified. Then, 250 μL of staining solution was added to each well, and the cells were incubated in the dark for 30 min. Images were acquired using a confocal laser scanning microscope.
[0055] (5) Detection of mitochondrial membrane potential MC3T3-E1 cells were loaded at a rate of 1×10⁶ cells per well. 5 Cells were seeded at a density of [number] cells per well in 12-well plates and treated with different methods. Mitochondrial membrane potential was assessed using the JC-1 Mitochondrial Membrane Potential Assay Kit (C2006, Beyotime). Cells were incubated with 5 μg / mL JC-1 working solution for 30 min, followed by three washes to remove unbound probes. Fluorescence images were acquired using confocal microscopy. Mitochondria with normal membrane potential exhibited red fluorescence at approximately 590 nm, while mitochondria with decreased membrane potential exhibited green fluorescence at approximately 530 nm.
[0056] (6) Tube formation experiment The angiogenic effect of UBMR@Zn synthesized according to the method in Example 1 was evaluated using a tube formation assay. Pre-chilled 24-well plates were coated with 250 μL of thawed Matrigel (211262, Nice, Wuxi, China) per well and incubated at 37°C for 1 h to allow gelation. EPCs were then placed in 5 × 10⁻⁶ cells per well. 4 Cells were seeded at a density of 1,000 cells into Matrigel-coated wells and treated accordingly. After 12 hours, tube formation was imaged under a microscope and quantified using ImageJ software.
[0057] (7) Scratch migration test Endothelial progenitor cells (EPCs) were seeded into 6-well plates and cultured for 24 h. A straight scratch was made in the center of each well using a 100 μL pipette tip. Cells were washed three times with PBS to remove detached cells and then subjected to designated treatments. Live cells were visualized using Calcein-AM (C2012, Beyotime). After 12 h, the closure of the scratch was observed using a confocal laser scanning microscope.
[0058] (8) Alkaline phosphatase and Alizarin Red S staining Alkaline phosphatase (ALP) and Alizarin Red S (ARS) staining were performed to assess osteogenic differentiation and matrix mineralization. MC3T3-E1 cells were seeded in 24-well plates and cultured in osteogenic induction medium under different treatment conditions. ALP staining was performed 7 days after osteogenic induction using an ALP staining kit (C3250S, Beyotime Biotechnology). Calcium deposition and matrix mineralization were assessed 21 days after induction using ARS staining solution (ALIR-10001, Cyagen Biosciences, Guangzhou, China).
[0059] (9) Transwell migration experiment The migration ability of MC3T3-E1 cells and EPCs was assessed using Transwell chambers (3422, Corning Costa, Corning Incorporated, USA) with an 8.0 μm pore size. Cells were loaded at 1 × 10⁶ cells per well. 5 Cells were seeded at a density of 1000 mcg in the upper chamber and treated with different methods. After 12 h, residual cells on the upper surface of the membrane were gently removed, while cells that migrated to the lower surface were fixed with 4% paraformaldehyde and stained with crystal violet for 30 min. After washing, the migrated cells were observed using an inverted optical microscope.
[0060] (10) RT-qPCR Total RNA was extracted from MC3T3-E1 cells after different treatments using an RNA isolation kit (RC112, Novizan, Nanjing, China). Reverse transcription was performed using PrimeScript RT Master Mix (RR092A, Takara Bio, Shiga, Japan). RT-qPCR was performed using a CFX Connect real-time PCR detection system (Bio-Rad, Hercules, USA). The primer sequences used for RT-qPCR are listed in Table 1.
[0061] Table 1 Primer sequences used for RT-qPCR 4. Rats with ORNJ model and in vivo treatment (1) Model building The male Sprague-Dawley (SD) rats used in the experiment were provided by the Laboratory Animal Center of the Fourth Military Medical University. This animal research protocol has been approved by the Institutional Animal Care and Use Committee of the Fourth Military Medical University (Approval No.: IACUC-2024-kq-044), and all procedures were strictly in accordance with the institutional animal care guidelines.
[0062] Rats were randomly divided into five groups: control group, ORNJ group, ORNJ+UBMR group, ORNJ+BMR@Zn group, and ORNJ+UBMR@Zn group. The control group received only extraction of the left mandibular first molar without radiation therapy or implantation. The ORNJ group received 8 Gy of radiation therapy daily for 5 consecutive days, followed by extraction of the left mandibular first molar on day 9 without implantation. The ORNJ+UBMR group received UBMR (unmineralized composite material) implantation during extraction, in addition to the ORNJ group treatment. The ORNJ+BMR@Zn group received BMR@Zn (unadded UCNPs composite material) implantation during extraction, in addition to the ORNJ group treatment. The ORNJ+UBMR group received UBMR@Zn (complete composite material) implantation during extraction, in addition to the ORNJ group treatment.
[0063] For the NIR-responsive treatment protocol, all rats underwent 20-minute, three-times-daily irradiation of the left mandibular region with a 980 nm NIR laser (300 mW / cm²) for two weeks following tooth extraction. Four weeks later, prior to sacrifice, rats were intraperitoneally injected with 60 mg / kg pipemnidazole to label hypoxic tissues. Euthanasia was performed 30 minutes later via an overdose of sodium pentobarbital, and mandibular specimens were collected for further analysis.
[0064] (2) Blood perfusion assessment Prior to sacrifice, rats were anesthetized with isoflurane and the hair in the mandibular region was removed. Blood perfusion in the mandibular region was assessed using a laser speckle flow imaging system (RFLSI ZW, Reward Life Sciences, Shenzhen, China). Perfusion images were acquired using the same imaging conditions in all groups, and relative blood perfusion was quantified in the region of interest in the mandible.
[0065] (3) Micro-CT analysis Mandibular samples were scanned using a micro-computed tomography system (AX-2000, Always Imaging, Ningbo, China). Regions of interest were defined around extraction sockets in the rat mandibles. Bone regeneration was quantitatively analyzed using standard morphometry parameters, including bone mineral density, bone volume fraction, trabecular thickness, and trabecular number.
[0066] (4) Histological and immunostaining analysis Mandibular bone specimens were first fixed in 4% (w / v) paraformaldehyde for 24 hours, followed by decalcification in 10% (w / v) EDTA for 8 weeks. After decalcification, the specimens were embedded, sectioned, and then stained with hematoxylin and eosin (H&E), Masson's trichrome stain, immunohistochemical stain, and immunofluorescence stain. H&E staining was used to assess bone repair; Masson trichrome staining was used to detect collagen deposition; tissue hypoxia was assessed by hypoxia-inducible factor-1α (HIF-1α) immunofluorescence assay (YT2133, Immunoway, Suzhou, Jiangsu) and by pimonidazole immunohistochemistry using the Hypoxyprobe Omni kit (HP3-XXX, Hypoxyprobe, Burlington, Massachusetts, USA); angiogenesis and osteogenic processes were detected by immunofluorescence staining of differentiation cluster 31 (CD31; YM8207, Immunoway) and Runt-related transcription factor 2 (RUNX2; YM8347, Immunoway), respectively; at the end of the experiment, major organs such as lung, liver, spleen, kidney and heart were collected to assess systemic biocompatibility. These organs were fixed in 4% paraformaldehyde, embedded in paraffin, sectioned and observed by H&E staining.
[0067] 5. Statistical Analysis Unless otherwise stated, all experiments were independently repeated at least three times. Quantitative analyses were performed using independent biological samples; repeated measurements on the same sample were avoided unless technically required. Sample sizes were determined based on standard operating procedures, preliminary data, and ethical considerations. All data are expressed as mean ± standard deviation (SD). Normality was assessed using the Shapiro-Wilk test, and homogeneity of variance was determined using the modified Levene test. When these statistical assumptions were not met, the datasets were logarithmically transformed before using parametric statistical methods to satisfy the assumptions. Statistical analysis and graphing were performed using GraphPad Prism version 10.1.2 (GraphPad Software, Boston, Massachusetts, USA). Studentt's test was used for comparisons between two groups, and one-way or two-way ANOVA was used for comparisons among multiple groups, depending on the circumstances. The statistical significance level was set at α = 0.05.
[0068] II. Results 1. Design and preparation of UBMR@Zn composite materials This UBMR@Zn composite material was prepared using biomimetic mineralization and microfluidic encapsulation technology, enabling staged treatment of ORNJ ( Figure 1 (a) In PCC 7942, the negatively charged surface first attracts Zn through electrostatic interaction. 2+ The ions provide nucleation sites for the subsequent growth of zinc-based biomineralized layers. The resulting PCC@Zn was then mixed with UCNPs and AlgMA, and formed hydrogel microspheres after microfluidic droplet generation and UV crosslinking treatment.
[0069] By evaluating different Zn 2+ The survival rate and zinc loading capacity of PCC 7942 at different concentrations determined the optimal Zn²⁺ concentration required for mineralization. Since chlorophyll a has a characteristic absorption peak at 680 nm, OD... 680 It was used as an indirect indicator of PCC 7942 growth and photosynthetic activity. The OD value was measured continuously for 7 days after mineralization. 680 Monitoring revealed that when the Zn²⁺ concentration was 20 μM or lower, the survival rate of PCC 7942 was comparable to that of the untreated control group; higher concentrations led to a significant decrease in survival rate. Figure 1 (b) Inductively coupled plasma mass spectrometry analysis showed that the zinc loading per mL of PCC 7942 suspension increased with increasing Zn²⁺ concentration: reaching 1.13 μg / mL at 20 μM, and decreasing at 25 μM. These results indicate that 20 μM Zn²⁺ can maintain the activity of PCC 7942 while achieving a high zinc loading capacity. Figure 1 (c) Therefore, subsequent experiments all used a Zn²⁺ concentration of 20 μM.
[0070] Zeta potential measurements showed that the surface potential of natural PCC 7942 changed from −35.18 mV to −6.90 mV after mineralization, indicating that the surface mineralization process was successfully completed. Figure 1 (d in the text). Transmission electron microscopy revealed that the originally smooth surface of the mineralized PCC 7942 (PCC@Zn) was covered by a distinct and dense mineral layer. Figure 1 (e). Energy dispersive spectroscopy further confirmed that zinc is uniformly distributed on the cell surface. The X-ray diffraction pattern of PCC@Zn showed a broad amorphous background peak originating from the PCC 7942 biomatrix, superimposed with multiple weak diffraction peaks (including peaks attributable to hydrated zinc phosphate). Figure 1 (f in the text). These results indicate that zinc is primarily immobilized on the PCC 7942 surface through the formation of a mineral layer mainly composed of hydrated zinc phosphate. Oxygen production experiments show that the mineralization process did not affect the oxygen production activity of PCC 7942 (f in the text). Figure 1 g in (the middle part).
[0071] Subsequently, near-infrared responsive UCNPs (NaYF4:Yb) were synthesized. 3+ Er 3+ Under 980 nm excitation light, these UCNPs exhibited a strong emission peak at 680 nm. This emission peak highly overlapped with the absorption range of PCC 7942 chlorophyll, indicating its highly efficient optical activation ability. Figure 1 (h in the text). Subsequently, PCC@Zn and UCNPs were co-encapsulated in AlgMA hydrogel microspheres using a microfluidic platform. Figure 1 (i). The microsphere composition was optimized by screening for oxygen production at different PCC@Zn and UCNPs concentrations; at 5×10 6 The highest oxygen production was achieved at 7942 PCC cells / mL and 60 mg / mL UCNPs. This formulation was used in all subsequent experiments. Figure 1 j in the middle.
[0072] The optimized UBMR@Zn was then characterized. Under a fluorescence microscope, PCC 7942 exhibited inherent red autofluorescence; after assembly, under a bright-field microscope, UBMR@Zn was observed to be spherical and uniform in shape, with PCC 7942 evenly distributed within the hydrogel matrix; the corresponding fluorescence image showed a red signal originating from the autofluorescence of PCC 7942, indicating that PCC7942 was successfully encapsulated within UBMR@Zn. Figure 1 (k in the text). Dimensional analysis shows that the average diameter of UBMR@Zn is 224.5 μm ± 12.39 μm, proving that the microfluidic preparation process has good uniformity. Figure 1(l); Scanning electron microscopy (SEM) further confirmed the formation of UBMR@Zn and showed that rod-shaped PCC 7942 were distributed inside the hydrogel network and exposed on the surface (l); Figure 1 (m in the middle).
[0073] 2. Functional characterization of UBMR@Zn First, the long-term viability of PCC@Zn was evaluated by co-encapsulating PCC@Zn and UCNPs into AlgMA microspheres. Fluorescence imaging results at different time points showed that PCC@Zn maintained a high survival rate of up to 14 days within UBMR@Zn. Figure 2 a and Figure 2 (b) Subsequently, 2′,7′-dichlorodihydrofluorescein (DCFH) was used as an indirect fluorescent probe for the generation of oxygen-associated reactive oxygen species (ROS) to evaluate the photosynthetic oxygen production function of the microspheres: when oxidized by ROS, the non-fluorescent DCFH is converted into 2′,7′-dichlorofluorescein (DCF), which emits green fluorescence, indicating that photosynthesis is activated. BMR@Zn containing PCC@Zn but without UCNPs was used as a control to evaluate the UCNP-mediated upconversion effect; under NIR illumination, the DCF fluorescence signal of UBMR@Zn was significantly stronger than that of BMR@Zn (…). Figure 2 (c) indicates that UCNP-mediated upconversion can effectively activate photosynthetic oxygen production.
[0074] A two-stage scheme controlled by NIR irradiation was used to achieve sequential oxygen and zinc release. UBMR@Zn was irradiated daily for the first two weeks to promote oxygen generation; then NIR irradiation was stopped for the following two weeks to promote zinc release. Figure 2 (d in the original text). The timing characteristics of oxygen and Zn²⁺ release were then monitored: under 60 min daily NIR illumination, the oxygen concentration rose rapidly in the early stages and remained at a high level; as the mineralized shell gradually dissolved, zinc release became more significant at subsequent time points. These results indicate the existence of a phased release pattern—initial provision of oxygen followed by delayed release of Zn²⁺ (d in the original text). Figure 2 (e in the text).
[0075] Cellular function of UBMR@Zn was evaluated using an in vitro simulated environment. Figure 2 (f) Pre-irradiated MC3T3-E1 cells were co-cultured with 100 mg / mL UBMR@Zn in a Transwell system under hypoxic conditions containing 1% (v / v) O2 to simulate the hypoxic microenvironment of ORNJ. Intracellular hypoxia staining showed that the hypoxic fluorescence intensity was reduced in cells co-cultured with NIR-irradiated UBMR@Zn (f). Figure 2 g and Figure 2The results indicate that the oxygen produced by UBMR@Zn can effectively diffuse into cells and alleviate hypoxic stress. To further evaluate the delayed Zn²⁺ release from UBMR@Zn, UBMR@Zn was pre-incubated in PBS for 14 days to induce Zn²⁺ release. These late-stage UBMR@Zn cells were then co-cultured with pre-irradiated MC3T3-E1 cells, and intracellular Zn²⁺ levels were detected using a zinc-sensitive fluorescent probe. Consistent with previous reports, the Zn²⁺ level in irradiated cells was lower than in normal cells; however, treatment with late-stage UBMR@Zn enhanced the Zn²⁺ fluorescence signal in irradiated cells (h). Figure 2 i and Figure 2 The j in the figure indicates that UBMR@Zn releases Zn²⁺ in the later stages after a long incubation period.
[0076] 3. Effects of sequential delivery of oxygen and zinc via UBMR@Zn on in vitro cell rescue, angiogenesis activity, and osteogenic activity. This invention employs a time-phased in vitro treatment protocol to simulate a continuous oxygen-zinc delivery regimen: freshly prepared UBMR@Zn represents the early oxygen production phase; UBMR@Zn pre-incubated in PBS for 14 days represents the late Zn²⁺ release phase. This design allows for the evaluation of the key functional properties of UBMR@Zn at each phase within a limited timeframe for in vitro experiments.
[0077] Under combined radiation and hypoxic stress conditions, all experimental groups were exposed to 980nm NIR light for 60 min daily. UBMR group cells were treated with freshly prepared UBMR containing unmineralized PCC 7942 and UCNPs; BMR@Zn group cells were treated with BMR@Zn pre-incubated with PBS for 14 days; UBMR@Zn group cells were co-cultured with freshly prepared UBMR@Zn in the first half of the experiment, and then replaced with UBMR@Zn pre-incubated with PBS for 14 days in the second half, thus simulating a continuous oxygen production and Zn²⁺ release phase.
[0078] First, the ability of UBMR@Zn to protect MC3T3-E1 cells from radiation damage was evaluated. Live / dead cell staining results showed that combined radiation and hypoxia treatment led to significant cell death in the ORNJ group. Figure 3 a and Figure 3 (b) The BMR@Zn group showed only limited protective effect, indicating that zinc stimulation alone is insufficient to reverse early damage caused by radiation and hypoxia. In contrast, both the UBMR and UBMR@Zn groups significantly maintained more surviving cells. Mitochondrial membrane potential (MMP) analysis showed significant depolarization in both the ORNJ and BMR@Zn groups, while the UBMR and UBMR@Zn groups maintained MMP better. Figure 3 c and Figure 3(d in the text). These results indicate that, under stress conditions similar to ORNJ, early oxygenation processes play a crucial role in maintaining cell viability and mitochondrial function, while zinc alone has limited effectiveness under these conditions.
[0079] The angiogenic activity of endothelial progenitor cells (EPCs) was then evaluated. Tube formation assays showed that the ORNJ, UBMR@Zn, and UBMR groups formed only limited capillary-like networks; while the UBMR@Zn group formed a denser and more interconnected vascular structure. Figure 3 e in Figure 3 f in the text). The scratch wound healing experiment further confirmed this angiogenesis-promoting effect: after 12 hours of culture, the UBMR@Zn group exhibited the strongest migration ability (f in the text). Figure 3 g and Figure 3 These results indicate that zinc stimulation alone is insufficient to improve angiogenesis defects under ORNJ-like stress, and simply increasing oxygen supply only brings limited improvement; while sequential application of UBMR@Zn treatment can more significantly enhance the migration and tubular formation capabilities of EPCs.
[0080] Osteogenic potential was finally assessed under the aforementioned treatment conditions. Alkaline phosphatase (ALP) staining and Alizarin Red S (ARS) staining results showed that the UBMR@Zn group exhibited the strongest osteogenic response, with higher ALP staining intensity and a greater number of mineralized nodules than other groups. Figure 3 i~ Figure 3 The results were further validated by quantitative real-time PCR: compared with the ORNJ group, the expression of the hypoxia marker HIF-1α was reduced in the UBMR@Zn group (l). Figure 3 The expression of osteogenic markers osterix (OSX), RUNX2, bone morphogenetic protein 2 (BMP2), and osteopontin (OPN) was increased in m). Figure 3 n~ Figure 3 (q in the text). In summary, these in vitro experimental data indicate that staged oxygen delivery followed by Zn²⁺ release can more effectively rescue irradiated cells and promote synergistic angiogenesis and osteogenic responses.
[0081] 4. Effects of UBMR@Zn on hypoxia and angiogenesis in vivo This invention establishes a rat ORNJ model for evaluating the in vivo therapeutic effect of staged oxygenation-zinc therapy. Figure 4(a) Six-week-old male Sprague-Dawley rats received fractionated partial irradiation of the mandible at a daily dose of 8 Gy for 5 consecutive days. On day 9, the left mandibular first molar was extracted, and the corresponding microspheres were implanted into the alveolar socket. The extraction site was irradiated with 980 nm NIR light for the first two weeks to activate the early oxygen production phase. Each irradiation lasted 20 minutes, three times a day. Subsequently, the animals were fed without NIR light for two weeks to promote the transition to the Zn²⁺-dominant repair phase. Experimental samples were collected at week 6.
[0082] Since local hypoxia is a typical feature of ORNJ, the researchers first used permonidazole immunohistochemistry (Phnomazol) Figure 4 b and Figure 4 c) and HIF-1α immunofluorescence staining method ( Figure 4 d and Figure 4 (e) The hypoxic microenvironment was examined. Strong positive signals for both biomarkers were detected in both the ORNJ and BMR@Zn groups, indicating persistent local hypoxia. The hypoxic signal in the UBMR group was weaker than that in the ORNJ group, but significant residual hypoxia still existed. The UBMR@Zn group showed the weakest signals of pimonidazole and HIF-1α among all treatment groups. These results indicate that UBMR@Zn treatment can more effectively and persistently improve the local oxygen microenvironment.
[0083] Further assessment of angiogenesis was conducted using immunofluorescence staining with the endothelial marker CD31. Figure 4 f and Figure 4 (g) Sparse and discontinuous CD31-positive vessels were observed in the ORNJ group; angiogenesis was similarly restricted in the BMR@Zn and UBMR groups. These results suggest that simply delaying Zn²⁺ delivery or simply early oxygenation is insufficient to promote significant vascular remodeling. In contrast, abundant and continuous CD31-positive vascular structures were observed within the defect area in the UBMR@Zn group.
[0084] Subsequently, the relationship between the recovery of CD31-positive vascular structures and local blood perfusion was assessed. Laser speckle contrast imaging showed severely impaired blood flow perfusion in the mandible of the ORNJ group. Figure 4 h and Figure 4 (i) The UBMR and BMR@Zn groups showed only slight improvement; in contrast, the UBMR@Zn group showed the most significant restoration of local blood flow. In summary, these results indicate that UBMR@Zn can alleviate radiation-induced hypoxia and promote in vivo vascular remodeling, a conclusion consistent with the design philosophy of UBMR@Zn, which employs staged oxygen delivery and delayed Zn²⁺ release.
[0085] 5. Effects of UBMR@Zn on fossa healing and bone regeneration in a rat ORNJ model At week 6 after assessing vascular recovery, the healing of the extraction socket and bone regeneration were observed. Gross oral examination revealed typical features of radiation-induced osteonecrosis in the ORNJ group, including delayed mucosal closure and exposure of necrotic bone; both the BMR@Zn and UBMR groups showed incomplete healing with persistent inflammatory changes; in contrast, the UBMR@Zn group had more adequate mucosal coverage of the extraction socket and healthier surrounding gingiva, indicating improved local wound healing. Figure 5 (a) in the middle.
[0086] Subsequently, micro-computed tomography (micro-CT) was used to perform three-dimensional reconstruction of the alveolar bone. Figure 5 (b) In the ORNJ group, most extraction sockets failed to heal, with very little new bone formation. This result indicates that bone repair function is severely impaired after tooth extraction following radiotherapy. In contrast, the UBMR@Zn group showed a dense and continuous trabecular bone structure, almost completely filling the defect area. Quantitative morphometric analysis further confirmed these observations. Figure 5 c~ Figure 5 (f) Compared with other groups, the UBMR@Zn group had significantly higher bone volume fraction (BV / TV), bone mineral density (BMD), trabecular bone number (Tb.N), and trabecular bone thickness (Tb.Th). These results indicate that UBMR@Zn treatment can effectively increase bone mass and improve the microstructure of regenerated bone.
[0087] Histological analysis further confirmed the imaging findings. Hematoxylin-eosin staining showed sparse and discontinuous trabeculae and poor lacunar filling in the ORNJ group. Figure 5 In the g); Masson trichrome staining showed limited collagen deposition and disordered matrix structure ( Figure 5 (h in the text). In contrast, UBMR@Zn treatment promoted more ordered woven bone formation and richer collagen matrix deposition within the defect area.
[0088] Osteogenic activity was further assessed by RUNX2 immunofluorescence staining. Figure 5 (i). Quantitative analysis showed that the RUNX2 expression level in the UBMR@Zn group was significantly higher than that in the ORNJ group, UBMR group, and BMR@Zn group (i). Figure 5 (j) These in vivo experimental results indicate that UBMR@Zn can effectively promote the healing of bone sockets and bone regeneration at the site of irradiated mandibular bone defects.
[0089] Systematic biosafety assessment of major organs such as the lungs, liver, spleen, kidneys, and heart was conducted using hematoxylin and eosin (H&E) staining. Figure 6The tissue structure of the UBMR@Zn group remained intact, with no obvious inflammatory infiltration, necrosis, hemorrhage, or structural damage observed. These results indicate that UBMR@Zn did not induce detectable systemic organ toxicity during the observation period.
[0090] Radiation-induced osteonecrosis of the jaw (ORNJ) is one of the most challenging complications following head and neck radiotherapy, characterized by a long-term damaged repair microenvironment marked by hypoxia, vascularization, and decreased cell density. This invention develops a photoresponsive biohybrid microreactor, UBMR@Zn, which addresses this pathophysiological process through a phased oxygen supply-angiogenesis-osteogenic strategy. Unlike traditional biomaterials with fixed bioactivity, UBMR@Zn is designed to possess adaptive therapeutic properties. This strategy allows UBMR@Zn to shift from simply supplementing oxygen to relying on Zn²⁺-mediated regenerative regulation, depending on the time progression of ORNJ repair. The results of this invention demonstrate that successful treatment of irradiated bone defects requires both the support of an osteoconductive scaffold and active repair of the damaged microenvironment.
[0091] The core feature of this platform lies in its photoresponsive oxygenation mechanism. Hypoxia is a typical manifestation of radiation-induced bone defects, primarily attributed to radiation-induced vascular damage, endothelial dysfunction, and reduced tissue perfusion. Existing data indicate that UBMR@Zn can alleviate hypoxia in the ORNJ-like microenvironment, improve cell viability, and maintain mitochondrial membrane potential, thereby enhancing cellular resistance to radiation-related damage. UBMR@Zn's oxygenation function differs from passive oxygen loading or burst oxygen release, as it relies on a photoregulated photosynthetic oxygen production process. By combining PCC 7942 with UCNPs, UBMR@Zn can convert tissue-penetrating NIR light into light energy usable for photosynthesis, thus achieving on-demand oxygen production at tissue-specific depths. This NIR-responsive design overcomes the penetration limitations of traditional visible light-activated photosynthesis systems and can provide controlled in-situ oxygen supplementation as an early microenvironment repair step before subsequent angiogenesis and osteogenic remodeling.
[0092] The biomaterial design of UBMR@Zn highlights the significant value of phased microenvironment regulation in repairing impaired biological functions. The core feature of UBMR@Zn lies in its sequential transition from oxygen production to Zn²⁺ release: early oxygen production partially alleviates hypoxia in irradiated bones, creating more favorable conditions for subsequent Zn²⁺-mediated regeneration. This sequential design, compared to the simultaneous release of multiple signaling molecules, is more suitable for wounds where hypoxia and poor vascular permeability are the main obstacles to repair. Its NIR-responsive component can also trigger the oxygen production process externally, thereby temporally regulating oxygen supply. This strategy, centered on microenvironment repair, is not only applicable to ORNJ but can also be extended to other ischemic or radiation-damaged lesions. These findings indicate that regenerative biomaterials for damaged tissues must first improve the local biological environment to achieve structural regeneration.
[0093] In summary, researchers have developed a biohybrid microreactor, UBMR@Zn, based on upconversion technology, designed to improve the hypoxic, vascularized, and low-cell-density microenvironment in ORNJ tissues. This platform combines early oxygen production with delayed Zn release. 2+ This combination forms a sequential oxygenation-angiogenesis-bone formation treatment model. This staged treatment approach effectively promotes vascular reconstruction and bone regeneration at the site of radiation-induced mandibular bone defects. After UBMR@Zn treatment, increased cell survival rate, enhanced angiogenic activity, and improved osteogenic differentiation capacity were observed. Based on the microenvironment regulation strategy of sequential oxygenation-angiogenesis-bone formation, a treatment plan centered on optimizing the microenvironment is provided for ORNJ repair and other ischemic or radiation-induced bone defects.
[0094] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. To avoid redundancy, this invention describes preferred embodiments.
[0095] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments, all of which fall within the scope of the invention.
Claims
1. A photosynthetic-mineralization biocomposite material, characterized in that, The photosynthetic-mineralized biocomposite material is prepared by encapsulating upconversion luminescent nanoparticles and biomimetic zinc mineralization-modified algal cells in a carrier matrix; the mass ratio of the upconversion luminescent nanoparticles, biomimetic zinc mineralization-modified algal cells and carrier matrix is 1:0.1~1.5:15~22. The upconversion luminescent nanoparticles are prepared by a hydrothermal method using rare earth nitrates, sodium citrate solution, and sodium fluoride solution as raw materials; the mass ratio of rare earth nitrates, sodium citrate, and sodium fluoride is 1:3~7:1~2. The biomimetic zinc mineralization modified algal cells are obtained by depositing a zinc-containing mineral shell on the surface of Synechococcus cells; The carrier matrix is sodium methacrylamide hydrogel microspheres formed by photocrosslinking and curing of sodium methacrylamide prepolymer.
2. The photosynthetic-mineralized biocomposite material according to claim 1, characterized in that, The particle size of the methacryloylated sodium alginate hydrogel microspheres is 200 μm to 250 μm.
3. The photosynthetic-mineralized biocomposite material according to claim 1, characterized in that, The density of the *Synechococcus* cells in the sodium methacrylate hydrogel microspheres was 10. 8 cells / mL ~10 11 The concentration of the upconversion luminescent nanoparticles in the sodium methacryloyl alginate hydrogel microspheres is 0.1 mg / mL to 100 mg / mL.
4. The photosynthetic-mineralized biocomposite material according to claim 1, characterized in that, The Synechococcus cells are slender Synechococcus ( Synechococcus elongatus ) PCC 7942 strain.
5. A pharmaceutical composition, characterized in that, It includes the photosynthetic-mineralized biocomposite material as described in any one of claims 1 to 4, and a pharmaceutically acceptable carrier.
6. The pharmaceutical composition according to claim 5, characterized in that, The dosage form of the pharmaceutical composition is selected from injectable microsphere suspensions, pre-formed three-dimensional scaffolds, or malleable bone filler pastes.
7. The method for preparing the photosynthetic-mineralized biocomposite material according to claim 1, characterized in that, Includes the following steps: Synechococcus cells were cultured to the logarithmic growth phase, and the culture was collected by centrifugation. The lower cell pellet was collected and resuspended in a Zn-containing solution. 2+ The algal cells modified with biomimetic zinc mineralization were stirred in a buffer solution for 12-48 hours. Then, sodium hydroxide solution was added to adjust the pH to 8.4-8.6, and the reaction was continued for 0.5-1.5 hours. The algal cells were then collected by centrifugation. Rare earth nitrates were added to sodium citrate solution and stirred to dissolve. Then, sodium fluoride solution was added to fluorinate the precipitate. After high-temperature reaction and washing of the precipitate, the upconversion luminescent nanoparticles were obtained. Algal cells modified with biomimetic zinc mineralization, upconversion luminescent nanoparticles, and sodium alginate prepolymerized solution were mixed and microdroplets were generated through a microfluidic device. After photocrosslinking and solidification, sodium alginate hydrogel microspheres encapsulating algal cells modified with biomimetic zinc mineralization and upconversion luminescent nanoparticles were formed. The methacrylamide sodium alginate hydrogel microspheres were collected, and the unencapsulated material was washed away to obtain the photosynthetic-mineralized biocomposite material.
8. The preparation method according to claim 7, characterized in that, The Zn-containing 2+ Zn in the buffer solution 2+ The concentration ranges from 0.1 μmol / L to 40 μmol / L.
9. The use of the photosynthetic-mineralized biocomposite material according to any one of claims 1 to 4 or the pharmaceutical composition according to claim 5 in the preparation of implantable materials for treating radiation-induced bone defects, radiation-induced osteonecrosis, osteoporotic fractures or ischemic osteonecrosis.